Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Lokasi Terhadap Kepuasan Pelanggan di Restoran I’am Geprek Bensu Harapan Indah - Nando, Iqbal Hernando; Hariadi Hadisuwarno (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2023)
This study aims to analyze the effect of product quality, service quality, and location on customer satisfaction at I'am Geprek Bensu Restaurant. The sample of this study consisted of 100 respondents who were active customers of the restaurant. Data were collected using questionnaires and analyzed using multiple linear regression analysis methods. The results showed that product quality, service quality, and location significantly affect customer satisfaction at I'am Geprek Bensu Restaurant. High product quality, including good taste, attractive presentation, and fresh raw materials, significantly influences customer satisfaction. In addition, good service quality, such as staff friendliness, responsiveness, and service efficiency, also contributes positively to customer satisfaction. These findings suggest that customers tend to feel more satisfied if they receive high-quality products and good service. Furthermore, the location of the restaurant also has a significant influence on customer satisfaction. The strategic location, easy access, and adequate parking facilities provide comfort and convenience for customers to visit the restaurant. These findings suggest that choosing the right location can improve customer satisfaction and reinforce a restaurant's positive image. This research makes an important contribution to understanding the factors that influence customer satisfaction in the restaurant industry. The results of this study guide the management of I'am Geprek Bensu Restaurant to improve product quality, service quality, and choose a strategic location to increase customer satisfaction